Maximising potential of methane production from biogas for power generation - Mohd Ghazi, Tinia Idaty; Muhammad Nasir, Ismail (Universiti Putra Malaysia Press, 2017)
Renewable energy projects in many developing countries need financial and legal back up from governments and other supportive bodies. There is a viable alternative to finite energy via usage of biomass waste a renewable energy source. The electrical energy production analysis on biomass waste presented in this paper is based on the experimental analysis carried out using the laboratory and pilot scale bioreactors. Electrical energy generated with oscillatory flow bioreactor (OFBR) was 10.12 kWh or up to 91% higher than the 10 L lab scale bioreactor (0.9 kWh), demonstrating that the novel OFBR has a great potential for renewable electricity. Also, the pilot scale plant achieves a value of 12.3 kWh, which the difference is not quite significant with that of OFBR. These results illustrate that the generation of the renewable electricity is feasible especially with the OFBR thereby achieving high methane potential during the treatment of manure and food waste. Nevertheless, energy recoveries should be enhanced to improve the entire operational performance.